Presenteeism in Nurses: Prevalence, Consequences, and Causes From the Perspectives of Nurses and Chief Nurses - Shan, Geyan; Wang, Shengnan; Wang, Wei; Guo, Shujie; Li, Yongxin (Frontiers in Psychiatry, 2021)
Presenteeism refers to the behaviour of people who turn up for work despite complaints of ill health that should prompt rest and absence from work. The high incidence of presenteeism in the nurse population has been extensively investigated using self-reported methods to explore its effects on individual outcomes. However, few studies have examined nurse presenteeism using an “other’s” perspective to verify self-reported information. Our aim in this study was to evaluate the prevalence, consequences, and causes of presenteeism in Chinese nurses from the perspectives of nurses and chief nurses. A sample of 481 nurses and 282 chief nurses from 5 hospitals in Henan Province, China, took part in this cross-sectional study. Participants completed the Sickness Presenteeism Questionnaire, Social Productivity Loss Questionnaire, and Causes of Nurse Presenteeism Questionnaire. The human capital method was used to estimate the monetary loss because of nurse presenteeism. We found that 94.25% and 82.08% of nurses experienced presenteeism in the past 6 months from the perspective of nurses and chief nurses, respectively. The annual monetary loss was estimated to be ¥4.38 billion and ¥2.88 billion based on the presenteeism reports from nurses and chief nurses, respectively. Workload, leave system, and conscientiousness are the main reasons for nurse presenteeism, and financial need is another important reason that is likely overlooked by chief nurses. This study provides a foundation for future research by presenting new knowledge about the prevalence, consequences, and causes of presenteeism in Chinese nurses. The findings emphasize the need for nursing managers and nursing departments to establish policy systems around paid sick leave, workload, and communication with managers to reduce nurse presenteeism and the subsequent socio-economic financial losses.